Functional brain architecture is associated with the rate of tau accumulation in Alzheimer’s disease - Nicolai Franzmeier (Nature Portfolio, 2020)
Tau accumulation is associated with disease progression in Alzheimer’s disease. Here the authors use resting state fMRI and tau-PET to demonstrate that baseline connectivity in Alzheimer's disease is associated with tau spreading.